PENGELOLAAN LEMBAGA PENDIDIKAN BERKOMPETENSI KEWIRAUSAHAAN DALAM PENINGKATAN KUALITAS - Aidatun Nisrina Nurul Firdaus; Iftitah Amin Suryani; Sukari (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
The management of educational institutions based on entrepreneurial competencies in quality improvement is that the application of this approach is able to enhance the competitiveness of students and develop an innovative and independent entrepreneurial spirit. Effective management, based on competencies, as well as the integration of entrepreneurial values in the curriculum and learning activities, will encourage the creation of graduates who are ready to face the challenges of the workforce and able to create new business opportunities. Thus, the management of educational institutions oriented toward entrepreneurial competencies significantly contributes to the improvement of education quality and the development of competent and highly competitive human resources